Oral health of patients on psychotropic medications: a study of outpatients in Queensland. (August 2013) - Lalloo, Ratilal; Kisely, Steve; Amarasinghe, Hemantha; Perera, Roshnal; Johnson, Newell
Objective: To describe the oral health of psychiatric patients on psychotropic medication, and compare this to Queensland and national data. Methods: We interviewed and examined 50 patients on medication at two outpatient clinics in South-east Queensland, in 2010. These areas had unfluoridated water till 2009. Results: One-third of the sample had not visited a dentist in the previous 2 years. One-half reported brushing their teeth once a day; 11% stated they never brushed. The mean of decayed, missing and filled teeth (DMFT) was 17.7 (95% confidence interval (CI) = 16.9 – 18.5), significantly higher than the state (13.1) and national (12.8) averages. Almost one-half of dental decay was untreated, compared to the state and national average of one-quarter. Conclusions: The oral health of this subgroup within the community is substantially worse than the general population and there are substantially greater treatment needs. Achieving equity in oral health care for these individuals has substantial resource and management implications.